موقع الفكر اللغوي العربي في الخطاب الديني لدى الزمخشري والكشاف نموذجا - Mohamed Sulthan Mohamed Saleem (Universitas Ahmad Dahlan, 2020)
This research is aimed to find the language exegetics in Zamakhsyari's attempt to interpret Al-Quran. He also expertise in the Arabic language, rhetoric, literature, and Islamic studies. He is also well-known as a Mu'tazilah scholar. This study tries to find the language aspects related to Zamakhsyari's explanation of religious discourse. According to Ibn Khaliikan, Zamakhsyari is a scholar in Arabic grammatical, language, poetry, and literature. He speaks standard Arabic fluently. Quran is the guidance for humankind, and it is inimitability. It also contains beautifulness in language and style. Hundreds of Mu'tazilah scholars had written interpretation of Al-Quran. However, one noticeable interpretation book that could provide a comprehensive explanation is an interpretation book written by Zamakhsyari known as al-Kashshaf. This study focuses on explaining Zamakhsyari's linguistic thought in interpreting the Quran.